"Strong, fearless, tough, enduring": Collegiate male wrestlers' perceptions of body image and masculinity. Issue 1 (February 2022) - Fasczewski, Kimberly S.; Powell, Sara M.; Stevens, Nolasco R.; Skinner, Jared W.
Abstract: Background: Successful wrestling performance is largely dictated by weight. Some wrestlers engage in rapid weight loss methods to maximize performance at lower weight classes. Data from other sports suggest these methods can negatively affect body image (BI) and physical health and put athletes at risk for disordered eating behaviors, but the actual impact in wrestling is unknown. The present study examined the relationship between perceptions of masculinity and BI to eating disorder (ED) risk in male collegiate wrestlers. Methods: Survey data were collected from active male NCAA wrestlers ( n = 63). Wrestlers completed the Eating Attitudes Test, the Multidimensional Body-Self Relations Questionnaire, the Hoffman Gender Scale, and three open-ended response items. Results: ED risk was positively correlated to appearance self-importance ( r = 0.361, p < 0.01) and body weight vigilance ( r = 0.618, p < 0.01) and negatively correlated to BI satisfaction ( r = -0.328, p < 0.05). Gender self-acceptance was correlated to lower importance placed on BI ( r = 0.402, p < 0.01). Additionally, 35 (53.9%) participants reported at least one maladaptive eating behavior (e.g. binging, vomiting, laxative use). Qualitative data indicates similarities in traits associated with successful wrestlers and the traditional ideal male (mental and physical strength, toughness, surpassing limits). Conclusions: The masculine traits exemplified by the sport of wrestling may negatively impact BI and encourage maladaptive eating and/or weight-control behavior and increase ED risk. The information in this study can be used to inform the development of safer weight loss practices and specialized educational programs for ED risk for wrestlers. This study highlights a need for further qualitative analysis of weight-control behaviors in collegiate wrestling.